Women's Experiences of Emotional Recovery from Childbirth-Related Perineal Trauma: A Qualitative Content analysis - Nahid Jahani shoorab; Masoumeh Mirteimouri; Ali Taghipour; Robab Latifnejad Roudsari (Shiraz University of Medical Sciences, 2019)
Background: The postpartum health care program in Iran is limited to the first six weeks of delivery and only focuses on women's physical problems. It seems that the issue of emotional recovery is underestimated in postnatal women with prenatal injuries. This study was designed to explore women's experiences of emotional recovery from childbirth-related perineal trauma. Methods: This qualitative content analysis was performed on 22 postnatal women with perineal trauma during labor at Omol-banin Hospital from the 20th of April to 25th of December in Mashhad, Iran in 2016. The participants were purposively selected between 10 days to one year after childbirth. Data were collected through semi-structured interviews and saturated after 26 interviews. The analysis of data was concurrently carried out using conventional content analysis adopted by Elo and Kyngas (2008). The MAXQDA software (Ver.10) was used for data organization. Results: Emotional recovery after birth trauma is defined as going on a journey from negative emotions to subjective well-being. Two super-ordinate generic categories emerged from the analysis: 1) feeling trapped in multifaceted issues, and 2) regaining possession of life. The participants encountered numerous concerns initially and with the help of family and community support, they regained the ability to dominate life and develop a pleasant mood. Improving physical functions had an essential role in regaining emotional well-being and enjoying daily life. Conclusion: The results of this study promoted our understanding of the emotional recovery in women with childbirth-related perineal trauma. This helps the caregivers to understand woman's emotional concerns and needs in order to offer appropriate counseling services.